Reconstruction with free flaps in robotic head-and-neck onco-surgeries - Arora, Rajan (Indian J Plast Surg, 2018)
AIMS AND OBJECTIVE: The aim of the present article is to highlight how reconstruction with free flaps is different and difficult in cases with robotic head-and-neck cancer surgery. It also highlights the technical guidelines on how to manage the difficulties. MATERIALS AND METHODS: Eleven patients with oropharyngeal cancer having undergone tumour excision followed by free-flap reconstruction been reviewed here. Nine patients had tumour excision done robotically through intraoral route while neck dissection done with transverse neck crease incision. There is a problem of difficult flap inset in this group of patient. Two patients had intraoral excision of tumour followed by robotic neck dissection via retroauricular incision. With no incision directly on the neck, microvascular anastomosis is challenging in this set of patients. Free flap was used in all the cases to reconstruct the defect. RESULTS: Successful reconstruction with free flap was done in all the cases with good outcome both functionally and aesthetically. CONCLUSION: Free-flap reconstruction is possible in robotic head-and-neck cancer surgery despite small and difficult access, but it does need practice and some technical modifications for good outcome.